Assessment of Cytomorphological Features and Risk of Malignancy of Bethesda Category III in Thyroid Cytopathology (Journal of Pathology of Nepal, 2025)
Background: In the Bethesda System for Reporting Thyroid Cytopathology, category III is characterized by architectural and nuclear features that are indeterminate. This category continues to pose diagnostic and therapeutic dilemmas, with a variable risk of malignancy across different populations.  Our study aimed to assess the risk of malignancy associated with Bethesda category III and the correlation of malignancy with each cytomorphologic feature within this category.Materials and Methods: All cases identified as Bethesda category III on fine needle aspiration cytology at The MES Medical College, Perithalmanna, India between January 2022 and September 2024 that had also had subsequent thyroidectomy at the same facility were retrospectively reviewed. The Ethical Committee gave its approval to the study (IEC/MES/F6/2025). In Bethesda Category III cytology, patient demographics, architectural characteristics, and cytological features were evaluated and compared to the final histopathological diagnosis in resected tissues.Results: Nuclear atypia was observed in 29 (61.7%) of the 47 Bethesda category III cases, with a 51.7% risk of malignancy. Features such as nuclear pseudo-inclusion (Risk of Malignancy-100%), membrane irregularity (p = 0.013), microfollicular pattern (p = 0.001), and crowded three-dimensional clusters (p = 0.003) were associated with an increased risk of malignancy. Conclusions: Risk of malignancy varies with different cytomorphological features, even within the AUS category. It is important to identify the nuclear and architectural features associated with a higher risk of malignancy and highlight them in the cytopathology report, which will help the clinician in patient management.